Serum lactate as a predictor of mortality after paediatric cardiac surgery. Issue 3 (1st September 1997) - Hatherill, M; Sajjanhar, T; Tibby, S M; Champion, M P; Anderson, D; Marsh, M J; Murdoch, I A
Abstract : OBJECTIVE: To assess the value of sequential lactate measurement in predicting postoperative mortality after surgery for complex congenital heart disease in children. DESIGN: Prospective observational study. SETTING: Sixteen bedded paediatric intensive care unit (PICU). SUBJECTS: Ninety nine children ( 90 survivors, nine non-survivors). MEASUREMENTS: Serum lactate and base deficit were measured on admission and every six hours thereafter. Data were analysed by Mann-Whitney and Fisher's exact tests. RESULTS: There was considerable overlap in initial lactate values between the survivor and non-survivor groups. Initial lactate was significantly raised in non-survivors (median 8.7, range 1.9–17.6 mmol/l) compared with survivors (median 2.4, range 0.6–13.6 mmol/l) (p = 0.0002). Twenty one patients (21.1%) with initial lactate concentrations greater than 4.5 mmol/l survived to PICU discharge. Using receiver operating characteristic analysis an initial lactate of 6 mmol/l had the optimum predictive value for mortality. Initial postoperative serum lactate >6 mmol/l predicted mortality with sensitivity 78%, specificity 83%, and positive predictive value of only 32%. CONCLUSION: Initial lactate concentrations have poor positive predictive value for mortality. The routine measurement of lactate for this purpose cannot be justified in clinical practice.